Incubation-Transforming Agenda Under COVID-19 Pandemic Canopy: A Framework for Private School Teacher Professional Development (TPD) - Chok, Koon Lan; Hock, Oo Yu (2020)
The persistence of life-threatening coronavirus pandemic worldwide paints an ominous outlook characterized by a haze of depression-extended uncertainties and pessimistic speculations. But it is not completely hopeless because the COVID-19 canopy provides an insidious respite for self-reflection beyond previous non-COVID 19 normal. Under new normal COVID-19 experiences is a window of life-relearning opportunity to review and plan-execute gestation ideas or development projects in anticipatory good times to come. And life-relearning under any circumstance is directly or indirectly live-education in transition. Defined as the delivery and application of knowledge, education as always requires the teaching community as a catalytic transformer for school-processing knowledge, and a major conduit of transmitting student-acquired knowledge often in the national language of the country, supported by the lingua franca – the English language – of international business and global communication. In this regard therefore the proposed 10-principle pathway TPD (Teacher Professional Development) Framework is share-reflected to engage discourse exchange-feedback on its viability and efficacy to transform private independent secondary school novice teachers into professional teachers in Malaysia, whose professionalism is benchmarked by 3-criteria vocation-relevant set of knowledge update, upskill competency and ethics accountability to further value-add and value-create in the public interest of private schooling contribution to building a formidable Malaysian nation.